Individual variation in age‐dependent reproduction: Fast explorers live fast but senesce young?. Issue 2 (13th November 2019) - Dingemanse, Niels J.; Moiron, Maria; Araya‐Ajoy, Yimen G.; Mouchet, Alexia; Abbey‐Lee, Robin N.
Abstract: Adaptive integration of life history and behaviour is expected to result in variation in the pace‐of‐life. Previous work focused on whether 'risky' phenotypes live fast but die young, but reported conflicting support. We posit that individuals exhibiting risky phenotypes may alternatively invest heavily in early‐life reproduction but consequently suffer greater reproductive senescence. We used a 7‐year longitudinal dataset with >1, 200 breeding records of >800 female great tits assayed annually for exploratory behaviour to test whether within‐individual age dependency of reproduction varied with exploratory behaviour. We controlled for biasing effects of selective (dis)appearance and within‐individual behavioural plasticity. Slower and faster explorers produced moderate‐sized clutches when young; faster explorers subsequently showed an increase in clutch size that diminished with age (with moderate support for declines when old), whereas slower explorers produced moderate‐sized clutches throughout their lives. There was some evidence that the same pattern characterized annual fledgling success, if so, unpredictable environmental effects diluted personality‐related differences in this downstream reproductive trait. Support for age‐related selective appearance was apparent, but only when failing to appreciate within‐individual plasticity in reproduction and behaviour. Our study identifies within‐individual age‐dependent reproduction, and reproductive senescence, as key components of life‐history strategies that vary between individuals differing in risky behaviour. Future research should thus incorporate age‐dependent reproduction in pace‐of‐life studies. Abstract : Great tits differ in patterns of age‐dependent reproduction as a component of pace‐of‐life. Slow explorers produce stable clutch sizes throughout their reproductive lives. Fast explorers by contrast show age‐related increases followed by reproductive senescence. Age‐related reproduction therefore constitutes a key component of personality‐related life‐history variation.